EKSISTENSI MUHAMMADIYAH DI ERA DISRUPSI DIGITAL: INTEGRASI IDEOLOGI, TRANSFORMASI SOSIAL-BUDAYA, DAN MANAJEMEN KEPEMIMPINAN - Muh. Zakki Amrulloh; Jefri Mardiansyah A.; Ishomuddin; Budi Sunariyanto (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2026)
Muhammadiyah faces the challenges of digital disruption, radicalism, and generational shifts. This article analyzes the existence of Muhammadiyah through the integration of ideological belief, socio-cultural transformation, and leadership management systems. The method employed is a qualitative descriptive-analytical literature study, drawing on sources from journals, books, official documents, and digital platforms. Data analysis adapts the model of Miles, Huberman, and Saldaña. The main findings indicate that Muhammadiyah’s resilience is rooted in three dimensions: (1) theological belief that integrates faith, tajdīd, rationality, moderation, and social justice; (2) cultural transformation through the negotiation of purification with local wisdom, character education, the theology of Al-Ma’un, ecology, and ethical technology; and (3) collegial leadership management based on deliberation, cadre formation, autonomy, and professionalism. The contribution of this article lies in demonstrating that Muhammadiyah’s existence does not rely solely on its charitable enterprises, but also on an adaptive system of values and organization. In conclusion, Muhammadiyah remains existent by connecting these three dimensions; however, digital challenges and generational change require continuous strategic renewal. Future research should examine the empirical implementation of digitalization within Muhammadiyah’s charitable enterprises.